Collaborative Learning in Higher Education: Review - Nugroho, Nugroho; Haq, Ziyaul; Burhan, Mulya; Hadi, Irfan; Yogi Purnama (Literasi: Jurnal Ilmu Pendidikan, 2026)
This study explores the potential of collaborative learning in higher education as a means of strengthening students’ critical thinking, communication, and digital literacy skills—three competencies widely regarded as essential for success in the twenty-first century. Although collaborative approaches have long been discussed in educational theory, less attention has been given to how they simultaneously cultivate these interconnected skills in technology-rich environments. To address this gap, a systematic literature review was conducted following the PRISMA framework, examining peer-reviewed studies published between 2014 and 2023. The findings consistently indicate that well-designed collaborative learning environments foster deeper analytical reasoning, clearer communication, and more purposeful engagement with digital tools. These outcomes are most evident when collaboration is supported by structured group tasks, reflective dialogue, and meaningful integration of technology. Approaches such as team-based learning, shared virtual workspaces, and online discussion platforms enable students to negotiate ideas, evaluate evidence, and co-construct knowledge in ways that extend beyond traditional lecture formats. At the same time, the review highlights ongoing challenges, particularly in sustaining active participation in virtual settings and ensuring that collaboration remains substantive rather than superficial. In post-pandemic educational contexts, where blended and online learning have become commonplace, these issues are especially pressing. Overall, this study contributes practical insights for educators and curriculum designers seeking to develop targeted instructional strategies that not only promote academic achievement but also prepare students for the complex communicative and digital demands of contemporary professional life.